Biomarkers of Intestinal Permeability Are Influenced by Diet in Patients with Ulcerative Colitis—An Exploratory Study - Natasha Haskey; Maximillian Eisele; Andreina Bruno; Raylene A. Reimer; Munazza Yousuf; Lorian M. Taylor; Remo Panaccione; Subrata Ghosh; Maitreyi Raman (Diagnostics)
Background and Objectives: The disruption of the intestinal epithelial barrier leads to increased intestinal permeability (IP), allowing endotoxins and pathogens to enter the bloodstream contributing to chronic inflammation. Western diets are associated with increased IP, while diets rich in polyphenols, fiber, and omega-3 fats are linked to decreased IP. The relationship between diet, disease activity, and IP in ulcerative colitis (UC) is poorly understood. We evaluated the effects of serum zonulin and lipopolysaccharide-binding protein (LBP) and their relationship to dietary factors in UC. Methods: A cross-sectional analysis was conducted on 37 UC participants who had baseline measures of dietary intake, disease activity and serum. Serum LBP and zonulin levels were measured by ELISA. Spearman’s rank correlations explored relationships between baseline IP, diet, and disease activity. Results: The median age was 35 years (29–47 years), 54% were male, and 76% were in clinical remission or had mild disease activity (partial Mayo score ≤ 4). LBP was significantly correlated (p < 0.05) with disease activity (partial Mayo score (r = 0.31), and positively correlated with total fat (r = 0.42) and refined grains (r = 0.35), but negatively correlated with fruit consumption (r = −0.50) and diet quality (r = −0.33). Zonulin was negatively correlated with protein (r = −0.39), niacin (r = −0.52) and vitamin B12 (r = −0.45) with a trend for significance (p = 0.06) with body mass index (r = 0.32). Conclusions: Baseline LBP levels were correlated with disease activity markers and dietary factors, suggesting that it could be a useful biomarker for assessing disease activity and diet quality in UC. Further trials are needed to confirm these findings.